Personal – semantic characteristics of higher school students’ motivation - Serdiuk, Liudmyla (Social Welfare: Interdisciplinary Approach, 2012)
The article deals with the problem of motivation of studying and professional activities at the university that is urgent for the student’s age and the modern psychology. The motivation of studying and professional development is determined by an invariant set of personal properties that reflects self-relation as an integral quality of the individual. The influence of these properties (self-esteem, self-interest, self-confidence, self-acceptance, auto sympathy, self-understanding, expectation for the positive attitude of others) is mediated with the estimate value of training of the future specialist on the level of studying motivation. The necessity of purposeful work on the development of future specialists’ motivation of studying and professional activities is shown.